Peningkatan Kompetensi Pedagogi Guru dalam Mengelola Pembelajaran Menyenangkan Berbasis Digital melalui Pelatihan - Tia Ayu Ningrum; Nurmina Nurmina; Nikmah Hayati; Fifin Wildana (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
The high dropout rate is one of the problems that is very urgent to find a solution. Efforts are made to provide training to teachers to improve teachers' pedagogical competence in order to manage fun learning and motivate students so as to minimize the dropout rate. Therefore, the purpose of this paper is to explain how the effect of training can improve teachers' pedagogical competence and produce fun learning. The method used in this research is descriptive quantitative which in this paper shows the comparison of pre-test and post-test results. Data was obtained using a questionnaire instrument. The results of data processing show that there is a difference in the results of the pretest and posttest after attending training on teacher pedagogical competence in managing technology-based fun learning. This means that there is an effect of training on improving teacher competence and teacher ability in creating fun learning. For this reason, teachers need to be given training in order to improve the necessary competencies.